Sex-specific maternal programming of corticosteroid-binding globulin by predator odour. Issue 1964 (8th December 2021) - Abuaish, Sameera; Lavergne, Sophia G.; Hing, Benjamin; St-Cyr, Sophie; Spinieli, Richard L.; Boonstra, Rudy; McGowan, Patrick O.
Abstract : Predation is a key organizing force in ecosystems. The threat of predation may act to programme the endocrine hypothalamic–pituitary–adrenal axis during development to prepare offspring for the environment they are likely to encounter. Such effects are typically investigated through the measurement of corticosteroids (Cort). Corticosteroid-binding globulin (CBG) plays a key role in regulating the bioavailability of Cort, with only free unbound Cort being biologically active. We investigated the effects of prenatal predator odour exposure (POE) in mice on offspring CBG and its impact on Cort dynamics before, during and after restraint stress in adulthood. POE males, but not females, had significantly higher serum CBG at baseline and during restraint and lower circulating levels of Free Cort. Restraint stress was associated with reduced liver transcript abundance of SerpinA6 (CBG-encoding gene) only in control males. POE did not affect SerpinA6 promoter DNA methylation. Our results indicate that prenatal exposure to a natural stressor led to increased CBG levels, decreased per cent of Free Cort relative to total and inhibited restraint stress-induced downregulation of CBG transcription. These changes suggest an adaptive response to a high predator risk environment in males but not females that could buffer male offspring from chronic Cort exposure.